Tsunami vulnerability and damage assessment in the coastal area of Rabat and Salé, Morocco - A. Atillah; D. El Hadani; H. Moudni; O. Lesne; C. Renou; A. Mangin; F. Rouffi (Natural Hazards and Earth System Sciences, 2011)
This study, a companion paper to Renou et al. (2011), focuses on the application of a GIS-based method to assess building vulnerability and damage in the event of a tsunami affecting the coastal area of Rabat and Salé, Morocco. This approach, designed within the framework of the European SCHEMA project (www.schemaproject.org) is based on the combination of hazard results from numerical modelling of the worst case tsunami scenario (inundation depth) based on the historical Lisbon earthquake of 1755 and the Portugal earthquake of 1969, together with vulnerability building types derived from Earth Observation data, field surveys and GIS data. The risk is then evaluated for this highly concentrated population area characterized by the implementation of a vast project of residential and touristic buildings within the flat area of the Bouregreg Valley separating the cities of Rabat and Salé. A GIS tool is used to derive building damage maps by crossing layers of inundation levels and building vulnerability. The inferred damage maps serve as a base for elaborating evacuation plans with appropriate rescue and relief processes and to prepare and consider appropriate measures to prevent the induced tsunami risk.